Enhanced Glycogen Storage of a Subcellular Hot Spot in Human Skeletal Muscle during Early Recovery from Eccentric Contractions - Nielsen, Joachim (PLoS One, 2015)
Unaccustomed eccentric exercise is accompanied by muscle damage and impaired glucose uptake and glycogen synthesis during subsequent recovery. Recently, it was shown that the role and regulation of glycogen in skeletal muscle are dependent on its subcellular localization, and that glycogen synthesis, as described by the product of glycogen particle size and number, is dependent on the time course of recovery after exercise and carbohydrate availability. In the present study, we investigated the subcellular distribution of glycogen in fibers with high (type I) and low (type II) mitochondrial content during post-exercise recovery from eccentric contractions. Analysis was completed on five male subjects performing an exercise bout consisting of 15 x 10 maximal eccentric contractions. Carbohydrate-rich drinks were subsequently ingested throughout a 48 h recovery period and muscle biopsies for analysis included time points 3, 24 and 48 h post exercise from the exercising leg, whereas biopsies corresponding to prior to and at 48 h after the exercise bout were collected from the non-exercising, control leg. Quantitative imaging by transmission electron microscopy revealed an early (post 3 and 24 h) enhanced storage of intramyofibrillar glycogen (defined as glycogen particles located within the myofibrils) of type I fibers, which was associated with an increase in the number of particles. In contrast, late in recovery (post 48 h), intermyofibrillar, intramyofibrillar and subsarcolemmal glycogen in both type I and II fibers were lower in the exercise leg compared with the control leg, and this was associated with a smaller size of the glycogen particles. We conclude that in the carbohydrate-supplemented state, the effect of eccentric contractions on glycogen metabolism depends on the subcellular localization, muscle fiber’s oxidative capacity, and the time course of recovery. The early enhanced storage of intramyofibrillar glycogen after the eccentric contractions may entail important implications for muscle function and fatigue resistance.